Reception Students UMS against the Values of Nationalism in the Film Soekarno - Harsini, Sri; , Budi Santoso, S.Sos.,M.Si; , Joko Sutarso, SE., M.Si (2016)
One film as history up the theme about nationalism is a movie that called Soekarno made in 2013. In the film tell Soekarno a young male that fought against dutch Colonist and Japan to finance independence Indonesia. Dalam film Soekarno .When government Soekarno , figure nationalist Soekarno represent thought Islam and marxism .The figure of Soekarno a cult central recorded from a childhood to adult and how the figure of Soekarno had a role in kemerdekan of the republic of Indonesia. Soekarno in the film is described as the figure nationalist who want independence day and free from colonization.This research in a reception analysis qualitative , research reception analysis this focused on production , text and the context .The qualitative method is one of diskriptif without figures without effort build a proposition , a model or the theory bed on the data obtained in the study of the result that has been obtained by reearchers, can be concluded that respondents who researchers interview about reception value nationalism in the film Soekarno that is negotiated reading and dominant reading